PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI DIRI TERHADAP PRESTASI AKADEMIK MAHASISWA ADMINISTRASI NIAGA POLITEKNIK NEGERI MALANG - Masreviastuti Masreviastuti; Siti Nurbaya; Farida Akbarina (Adbis: Jurnal Administrasi dan Bisnis, 2020)
The aim of this study is determine the effect of leadership style and self motivation on student academic achievement. In order to obtain a comprehensive picture, the object of the research was all first and second level students both D3 and D4 Business Administration Department of the State Polytechnic of Malang. The results are expected to be used as input related to leadership style and self motivation towards student academic achievement.The concept of HR policies studied also needs to be understood by academics. For this reason, the results of this study will also be published in accredited scientific journals. Besides that, it needs to be realized in the form of teaching materials so it can be used as a reference in the teaching and learning process at the Business Administration Department of the State Polytechnic of Malang.